Impacts of climate change on mid‐twenty‐first‐century rainfall in Ireland: a high‐resolution regional climate model ensemble approach. (26th April 2017) - Nolan, Paul; O'Sullivan, John; McGrath, Ray
ABSTRACT: The impacts of climate change on precipitation over Ireland are assessed for the mid‐century period 2041–2060 using an ensemble of downscaled climate simulations, based on medium‐to‐low and high emission scenarios. Results show significant projected decreases in mean annual, spring and summer precipitation amounts by mid‐century. The projected decreases are largest for summer, with reductions ranging from 0 to 13% and from 3 to 20% for the medium‐to‐low and high emission scenarios, respectively. The frequencies of heavy precipitation events show notable increases of approximately 20% during the winter and autumn months. The number of extended dry periods is projected to increase substantially by mid‐century during autumn and summer. The projected increases in dry periods are largest for summer, with values ranging from 12 to 40% for both emission scenarios. Regional variations of projected precipitation change remain statistically elusive. Abstract : The impacts of climate change on precipitation over Ireland are assessed for the mid‐century period 2041–2060 using an ensemble of downscaled climate simulations, based on medium‐to‐low and high emission scenarios. Results show significant projected decreases in mean annual, spring and summer precipitation amounts by mid‐century. The frequencies of heavy precipitation events show notable increases of approximately 20% during the winter and autumn months. The number of extended dry periods is projected to increase substantially by mid‐century during autumn and summer.